POLA PENGELOLAAN KURIKULUM PENDIDIKAN DI ERA 4.0 - Made Adi Nugraha Tristaningrat (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
The concept of management often called by management is a social process that pertains to the entire human effort with the help of humans and other resources, using efficient and effective methods to achieve a predetermined goal. The management pattern of the curriculum is a cooperative, comprehensive, systemic, and systematic curriculum management system for referring to the achievement of the curriculum objectives that has been formulated. The scope of the curriculum management is the principle of the management process itself which in the process of implementing the curriculum has a point of similarity in the management process principle. So that the experts in implementing the curriculum conducted approaches with management science. Even when viewed from its vast scope, curriculum management is one of the disciplines that branched out on the curriculum. The principle that must be considered in implementing curriculum management is productivity, democratic, cooperative, and effectiveness and efficiency, and lead to the achievement of the vision, mission, and objectives that have been established in the curriculum. The management process based on management principles consist of planning, organizing, monitoring and assessment, as well as improvement.